Machine glazed paper and method for preparing machine glazed paper

By using machine-laden glossy paper with high content of softwood fiber and starch, combined with specific production methods and additives, the shape stability and sealing problems of traditional paper-based materials when replacing disposable plastic items are solved, achieving a harder and more Straight, more flexural resistant paper rod.

CN119452134APending Publication Date: 2025-02-14BILLERUD AB
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380050427.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-30
Filing Date
2023-06-29
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Traditional paper-based materials are difficult to replace disposable plastic items, such as cotton swabs and lollipops, mainly due to poor shape stability, insufficient sealing, and powder loss and passivation during processing.

Method used

Using machine glossy paper including cork fibers and starch, cork fibers account for 63 wt.% or more of the total fiber, starch content ranging from 0.1 wt.% to 2 wt.%, and control paper by specific production methods and additives. and fiber orientation to improve the paper's bending resistance and sealing properties.

Benefits of technology

It achieves harder, straighter and more flexural resistance of the paper rod, while reducing powder loss and passivation problems, improving the overall performance of the paper rod.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005213862790000101
    Figure BDA0005213862790000101
  • Figure BDA0005213862790000111
    Figure BDA0005213862790000111
Patent Text Reader

Abstract

The present disclosure relates to a machine glazed paper comprising cork fibers, the machine glazed paper comprising starch in an amount in the range of from 0.1 wt.% to 2 wt.% by weight of the dry weight of the machine glazed paper, the amount of cork fibers making up 63 wt.% or more of the total amount of fibers, and the machine glazed paper having a Cobb value in the range of from 20 gsm to 50 gsm, measured according to Standard Method ISO 535: 2014. The present disclosure also relates to a method of producing the machine glazed paper.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the field of machine glazed paper and methods for preparing the same. More specifically, the present disclosure relates to machine glazed paper for preparing paper sticks. Background Art

[0002] There is a growing need to reduce the use of single-use plastic items such as cotton buds and lollipop sticks.

[0003] In view of these requirements, there is a need to develop materials that can replace plastics in such items.

[0004] In addition to being one of the most abundant biopolymers on earth, cellulose has attracted considerable attention for its high strength and stiffness as well as features such as low weight, biodegradability and renewability. However, paper-based materials have traditionally been considered less suitable for replacing such disposable plastic materials, such as, for example, cotton swab sticks and lollipop sticks, because paper-based items are considered to have lower form stability compared to such plastic items. It is also difficult to achieve adequate sealing without including components that negatively affect the degradability of the item. Dusting and passivation have also been significant issues in processing machinery during the manufacture of such paper parts.

[0005] In view of the above, an object is to prepare improved materials suitable for preparing disposable paper sticks. Summary of the invention

[0006] The object of the present disclosure is to provide a paper which at least partially overcomes the above mentioned drawbacks. This is achieved by: a machine glazed paper according to claim 1, the use of a machine glazed paper according to claim 14, a paper stick comprising or consisting of a machine glazed paper according to claim 15, and a method for producing a machine glazed paper according to claim 16.

[0007] According to a first aspect, there is provided a machine glazed paper comprising softwood fibers and starch, the machine glazed paper comprising starch in an amount ranging from 0.1 wt.% to 2 wt.% by weight of the machine glazed paper dry weight, and the amount of softwood fibers being 63 wt.% or more of the total amount of fibers. The machine glazed paper has a Cobb value ranging from 20 gsm to 50 gsm, measured according to standard method ISO 535:2014.

[0008] There is an increasing demand and legal requirement to replace plastic disposable items, such as cotton swab sticks, with biodegradable alternatives. However, traditionally, paper-based materials have been considered less suitable for the manufacture of cotton swab sticks or the like, because they are considered to have lower shape stability compared to such plastic sticks. The inventors have found that by using a softwood fiber paper according to the present disclosure, which has a high starch content and fast water absorption, expressed as Cobb value, a paper particularly suitable for preparing paper sticks is achieved. The machine-glazed paper has improved sealing properties, and when preparing paper sticks with the paper according to the present disclosure, a harder stick is obtained, which has improved straightness (as seen in the length direction of the stick), but still resists bending of the stick without breaking. In addition, it has been surprisingly found that this combination of features at least partially solves the problem of powdering and hair loss when preparing paper sticks from the paper according to the present disclosure.

[0009] Machine-glazed papers include softwood cellulose fibers, also called long fibers. Under natural conditions, softwood cellulose fibers measure about 2 to 4 millimeters in length, compared to hardwood fibers, which range from about 0.5 to 1.5 millimeters. Common examples of softwood include pine, fir, spruce, larch, and cedar. In paper, softwood fibers are less than 2 mm after pulping.

[0010] The paper comprises long fibres which results in the production of paper sticks with improved resistance to bending and reduced dusting during the slitting operation. The inventors have found that a high starch content combined with a high and fast water absorption of the paper results in a paper with improved tensile strength and sealing properties during formation of paper sticks.

[0011] Both sides of the machine-glazed paper (ie, the glossy side and the non-glazed side of the machine-glazed paper) have a Cobb value in the range of 20 gsm to 50 gsm, measured according to standard method ISO 535:2014.

[0012] The machine glazed paper may have a Cobb value in the range of 24 gsm to 50 gsm, measured according to standard method ISO 535:2014. Optionally, in the range of 25 gsm to 45 gsm.

[0013] The machine glazed paper may comprise starch in an amount in the range of 0.2 to 2 wt.% by weight of the dry weight of the machine glazed paper, preferably in the range of 0.4 to 2 wt.% by weight of the dry weight of the machine glazed paper.

[0014] The Cobb value of the paper may be obtained by reducing the amount of sizing agent in the paper, such as to a level below 0.9 wt.%, optionally to a level below 0.5 wt.%. Preferably, the amount of sizing agent in the paper may be 0.3 wt.% or less, such as 0.1 wt.% or less. Optionally, the paper is free of alkyl ketene dimer (AKD) and alkenyl succinic anhydride (ASA).

[0015] The machine glazed paper may comprise rosin in an amount less than 1 wt. % based on the dry weight of the machine glazed paper, preferably in the range of 0.05 to 0.5 wt. %, more preferably in the range of 0.09 to 0.3 wt. % based on the dry weight of the machine glazed paper.

[0016] The machine glazed paper may include alum (aluminum sulfate) in an amount ranging from 0.1 wt.% to 1 wt.%, preferably in the range of 0.1 wt.% to 0.5 wt.%, based on the dry weight of the machine glazed paper.

[0017] The machine-glazed paper may comprise 4 wt.% or less filler, such as 3 wt.% or less filler, such as 2 wt.% or less filler, preferably 1 wt.% or less filler, more preferably 0.5 wt.% or less filler, even more preferably 0.2 wt.% or less filler, based on the total weight of the paper, preferably the machine-glazed paper contains no filler. The machine-glazed paper comprising softwood fibers and having a Cobb value according to the present disclosure comprising 4 wt.% or less filler based on the total dry weight of the paper is found to be advantageous in terms of dusting during cutting and dulling of cutting and slitting tools. It is also found to increase the stiffness of paper sticks produced from the paper.

[0018] Optionally, 65 wt.% or more of the fibers in the machine-glazed paper are softwood fibers, preferably 75 wt.% or more of the fibers in the machine-glazed paper are softwood fibers, more preferably 85 wt.% to 100 wt.% of the fibers in the machine-glazed paper are softwood fibers.

[0019] Optionally, 95 wt.% to 100 wt.% by weight of the fibers in the machine-glazed paper are softwood fibers, preferably 100 wt.% of the fibers in the machine-glazed paper are softwood fibers.

[0020] 65 wt.% or more of the fibers in machine-glazed paper are softwood fibers, such as 85 wt.% to 100 wt.% of the fibers in machine-glazed paper are softwood fibers, which has been found to be advantageous in terms of dusting during cutting of the paper and paper sticks formed from the paper according to the present disclosure.

[0021] The machine glazed paper may have a basis weight in the range of 35 gsm to 100 gsm, preferably in the range of 38 gsm to 85 gsm. It has been found that the machine glazed paper according to the present disclosure is particularly suitable for forming paper sticks within these ranges. When using machine glazed paper with a higher basis weight, stiffness increases, while when using a lower range, the process of making paper sticks is negatively affected because an increased number of windings is required, which increases the complexity and defect rate of the paper stick during processing.

[0022] The softwood fibres may be unbleached softwood fibres. It has surprisingly been found that by using unbleached softwood fibres during the manufacture of paper sticks, the sealing properties of the paper are improved.

[0023] The softwood fibers may alternatively be bleached softwood fibers or a mixture of bleached and unbleached softwood fibers.

[0024] Machine glazed paper may have a CD / MD ratio of 0.5. This provides an indication that the fibers of the machine glazed paper are oriented primarily in the MD direction. During slitting of the paper, when making paper sticks, this fiber orientation is found to be beneficial in reducing dusting.

[0025] Machine glazed papers may have an MD elongation of 0.5% to 2%, preferably an MD elongation of 1% to 1.9%, measured according to standard method ISO 1924 / 3. The fact that machine glazed papers exhibit an MD elongation of 0.5% to 2% enables the production of stiffer paper sticks with the paper according to the present disclosure.

[0026] The machine glazed paper may have a CD elongation of 1.5% to 6.5%, preferably a CD elongation of 2% to 5.5%, such as a CD elongation in the range of 2 to 4.5%, measured according to standard method ISO 1924 / 3. The fact that the machine glazed paper exhibits a CD elongation of 1.5% to 6.5% enables the production of a stiffer paper stick, which also resists bending without breaking.

[0027] The fact that the first side of the paper is machine glazed provides an enhanced seal for the paper when used as the inner side during the production of the paper stick. The non-glazed side of the machine glazed paper may have a roughness of 500 ml / min to 2000 ml / min, preferably in the range of 350 ml / min to 1500 ml / min. The fact that the second side (used as the outer side during the production of the paper stick) is a non-glazed side having a roughness of 350 ml / min to 2000 ml / min, such as 500 ml / min to 2000 ml / min, preferably in the range of 350 ml / min to 1500 ml / min, provides improved adhesion to, for example, the cotton part of a cotton swab by friction. It has also been found to provide an improved user feel.

[0028] The paper may be non-calendered, which provides increased roughness to the non-glazed side of the paper.

[0029] The machine glazed paper may have an air resistance in the range of 15 to 35 s, measured according to the standard method ISO 5636 "Paper and board - Determination of air permeability (mid range) - Part 5: Gurley method. The inventors surprisingly found that the sealing speed of the machine glazed paper is improved when the air resistance of the paper is in the range of 15 to 35 s.

[0030] Machine-coated papers can be used to make paper sticks, such as for earplugs or lollipop sticks.

[0031] According to a second aspect, the present disclosure relates to the use of the machine-glazed paper according to the first aspect for producing paper sticks.

[0032] According to a third aspect, the present disclosure relates to a paper stick, such as an earplug stick or a lollipop stick comprising or consisting of the machine-glazed paper according to the first aspect.

[0033] According to a fourth aspect, the present disclosure relates to a method for producing a machine-coated paper according to the first aspect, the method comprising the steps of:

[0034] - providing a suspension comprising softwood fibers and starch, the amount of starch being in the range of 0.1 wt.% to 2 wt.% based on the total dry weight, and the amount of softwood fibers being 63 wt.% or more of the total amount of fibers;

[0035] - forming a fibrous web of said suspension;

[0036] - dewatering the fiber web;

[0037] - coating the first side of the dewatered fiber web in a coating unit to form a machine coated paper having a Cobb value in the range of 20 gsm to 50 gsm, measured according to standard method ISO 535:2014.

[0038] The method may comprise a pre-drying step between the dewatering step and the glazing step, wherein the fiber web is pre-dried in the pre-drying step. The moisture content in the fiber web may be controlled in the pre-drying step and, if necessary, may be adjusted in the pre-drying step. Optionally, the moisture content is in the range of 40 to 60 wt.% when entering the glazing unit. This may be achieved, for example, by adjusting the speed and / or temperature of the drying cylinders.

[0039] The inventors have found that the adhesion to the cylinder in the glazing unit can be improved by controlling the moisture content of the fiber web in the pre-drying step and, if necessary, adjusting the moisture content of the fiber web to within a set moisture content range when entering the glazing unit. Poor adhesion / repulsion of the fiber web to the cylinder may result in uneven drying of the fiber web, and such uneven drying may result in higher roughness values, thereby impairing the sealing of the paper when making paper sticks. However, by controlling the moisture content in the fiber web in the pre-drying step and adjusting the moisture content when necessary, the adhesion to the cylinder as well as the roughness of the surface can be improved, which may result in improved sealing of paper sticks made from machine-glazed paper.

[0040] The roughness of the first side (ie, the polished side) may be in the range of 100 to 400 ml / min.

[0041] In the method for producing machine-glazed paper, 65 wt.% or more of the fibers in the machine-glazed paper may be softwood fibers, preferably 75 wt.% or more of the fibers in the machine-glazed paper are softwood fibers, more preferably 85 wt.% to 100 wt.% of the fibers in the machine-glazed paper are softwood fibers.

[0042] Optionally, 95 wt.% to 100 wt.% by weight of the fibers in the machine-glazed paper are softwood fibers, preferably 100 wt.% of the fibers in the machine-glazed paper are softwood fibers.

[0043] The machine glazed paper may comprise rosin in an amount less than 1 wt. % based on the dry weight of the machine glazed paper, preferably in the range of 0.05 to 0.5 wt. %, more preferably in the range of 0.09 to 0.3 wt. % based on the dry weight of the machine glazed paper.

[0044] The machine glazed paper may include alum (aluminum sulfate) in an amount ranging from 0.1 wt.% to 1 wt.%, preferably in the range of 0.1 wt.% to 0.5 wt.%, based on the dry weight of the machine glazed paper.

[0045] The machine-glazed paper may comprise 4 wt.% or less filler, such as 3 wt.% or less filler, such as 2 wt.% or less filler, preferably 1 wt.% or less filler, more preferably 0.5 wt.% or less filler, based on the total weight of the paper, preferably the machine-glazed paper contains no filler. The machine-glazed paper comprising softwood fibers and having a Cobb value according to the present disclosure comprising 4 wt.% or less filler based on the total dry weight of the paper is found to be advantageous in terms of dusting during cutting and dulling of cutting and slitting tools. It is also found to increase the stiffness of paper sticks produced from the paper.

[0046] The amount of filler can be measured by means of the ash content by the standard method ISO 1762:2001. The type of filler can be determined by Fourier transform infrared spectroscopy (FTIR).

[0047] In order to prepare machine-glazed papers according to the present disclosure in which the percentage of softwood fibers is so high and the percentage of fillers, sizing agents, etc. is very low or absent, it may be necessary to adjust the paper quality previously run in the paper machine to ensure that no fillers, sizing agents or non-softwood fibers from the previous paper quality are introduced into the fiber suspension via the wastewater.

[0048] The machine glazed paper may have a Cobb value in the range of 24 gsm to 50 gsm, measured according to standard method ISO 535:2014. Optionally, in the range of 25 gsm to 45 gsm.

[0049] Optionally, the suspension may comprise starch in an amount ranging from 0.2 wt.% to 2 wt.% by weight based on the total dry weight, preferably ranging from 0.4 wt.% to 2 wt.% by weight based on the total dry weight.

[0050] The softwood fibers in the suspension may be unbleached or bleached softwood fibers.

[0051] The softwood fibers may alternatively be bleached softwood fibers or a mixture of bleached and unbleached softwood fibers.

[0052] A machine-glazed paper may have a CD / MD ratio of 0.5. This indicates that the fibers of the machine-glazed paper may be oriented primarily in the MD direction, such as 75 wt. % of the fibers of the machine-glazed paper are oriented in the MD direction.

[0053] The second side of the machine glazed paper may have a roughness of 350 ml / min to 2000 ml / min, optionally in the range of 500 ml / min to 2000 ml / min, preferably in the range of 350 ml / min to 1500 ml / min. This provides improved adhesion to, for example, the cotton part of a cotton swab by friction. It has also been found to provide an improved user feel. DETAILED DESCRIPTION

[0054] Thus, the present disclosure relates to machine-glazed paper comprising softwood fibers and starch. The majority of the fibers of the machine-glazed paper are softwood fibers, i.e. 63 wt.% or more, or 65 wt.% or more, or 85 wt.% to 100 wt.%, more preferably 95 wt.% to 100 wt.% of the fibers by weight in the machine-glazed paper are softwood fibers, such as 100 wt.% of the fibers. The machine-glazed paper comprises starch in an amount in the range of 0.1 wt.% to 2 wt.% by weight of the dry weight of the machine-glazed paper. In addition, the machine-glazed paper has a Cobb value in the range of 20 gsm to 50 gsm.

[0055] The Cobb value is measured according to the standard method ISO 535: 2014. The Cobb value provides information on the water absorption capacity of a paper sample and determines the amount of water absorbed by a defined area of ​​paper through single-sided contact with water in a certain period of time.

[0056] The machine glazed paper may have a Cobb value in the range of 24 gsm to 50 gsm, measured according to standard method ISO 535:2014. Optionally, in the range of 25 gsm to 45 gsm.

[0057] When testing machine-coated paper, each side shall be tested and meet the Cobb value, i.e. in contact with water during the measurement, the exposure time of the test is 60 seconds and the test area is 100cm 2 Prior to testing, the machine glazed papers were conditioned at a temperature of 23°C and 50% of RT.

[0058] The machine glazed paper may comprise starch in an amount in the range of 0.2 to 2 wt.% by weight of the dry weight of the machine glazed paper, preferably in the range of 0.4 to 2 wt.% by weight of the dry weight of the machine glazed paper.

[0059] The machine glazed paper may comprise rosin in an amount less than 1 wt. % based on the dry weight of the machine glazed paper, preferably in the range of 0.05 to 0.5 wt. %, more preferably in the range of 0.09 to 0.3 wt. % based on the dry weight of the machine glazed paper.

[0060] The machine glazed paper may include alum (aluminum sulfate) in an amount ranging from 0.1 wt.% to 1 wt.%, preferably in the range of 0.1 wt.% to 0.5 wt.%, based on the dry weight of the machine glazed paper.

[0061] The machine-glazed paper may comprise 4 wt.% or less filler, such as 3 wt.% or less filler, such as 2 wt.% or less filler, preferably 1 wt.% or less filler, more preferably 0.5 wt.% or less filler, based on the total weight of the paper, preferably the machine-glazed paper contains no filler. The machine-glazed paper comprising softwood fibers and having a Cobb value according to the present disclosure comprising 4 wt.% or less filler based on the total dry weight of the paper is found to be advantageous in terms of dusting during cutting and dulling of cutting and slitting tools. It is also found to increase the stiffness of paper sticks produced from the paper.

[0062] The amount of filler can be measured by means of the ash content by the standard method ISO 1762:2001. The type of filler can be determined by Fourier transform infrared spectroscopy (FTIR).

[0063] The bending resistance of paper is measured herein according to the standard method ISO 2493-1.

[0064] The Cobb value of the paper as disclosed herein can be obtained by using a small amount of sizing agent in the paper in combination with adding starch in an amount as disclosed herein. The machine-glazed paper may include a sizing agent in an amount of less than 0.9 wt.%, such as a level less than 0.5 wt.%. The paper may be free of alkyl ketene dimer (AKD) and alkenyl succinic anhydride (ASA). Optionally, the machine-glazed paper includes rosin, and the amount of rosin is less than 0.5 wt.%, preferably in the range of 0.05 wt.% to 0.5 wt.%, and more preferably in the range of 0.09 wt.% to 0.3 wt.%, based on the dry weight of the machine-glazed paper. The present disclosure also relates to a method for producing a machine-glazed paper as disclosed herein, the method comprising the steps of:

[0065] - providing a suspension comprising softwood fibers and starch, the amount of starch being in the range of 0.1 wt.% to 2 wt.% based on the total dry weight, the amount of softwood fibers being 63 wt.% or more of the total amount of fibers;

[0066] - forming a fibrous web of said suspension;

[0067] - dewatering the fiber web; and

[0068] - coating the first side of the dewatered fiber web in a coating unit to form a machine coated paper having a Cobb value in the range of 20 gsm to 50 gsm, measured according to standard method ISO 535:2014.

[0069] Optionally, the method comprises a pre-drying step between the dewatering step and the glazing step, wherein the fiber web is pre-dried in the pre-drying step to have a moisture content in the range of 40 to 60 wt.%.

[0070] The present disclosure also relates to the use of a machine glazed paper as disclosed herein for producing paper sticks.The paper sticks may be used, for example, as earplugs or lollipop sticks.

[0071] A method of forming a paper stick from a machine-coated paper as disclosed herein comprises the following steps:

[0072] - cutting the machine-glazed paper into asymmetric strips, the strips being asymmetric in the length direction (corresponding to the machine direction of the paper) and having a width that gradually increases from a first longitudinal edge of the strip to a second longitudinal edge of the strip;

[0073] - forming a groove in the paper strip from a first longitudinal edge to a second longitudinal edge of the paper strip;

[0074] - rolling up the paper strip, such as between a roller and a counterpart, thereby forming a rolled paper stick;

[0075] - Wetting and slitting the rolled paper sticks; and

[0076] - The moistened and cut paper sticks are dried.

[0077] The cut paper strips may have a length (as measured in the machine direction of the machine glazed paper) of about 60 to 80 mm, optionally 65 to 75 mm, and a width (as measured in the cross direction of the machine glazed paper) of about 250 to 350 mm, optionally 280 to 320 mm. Alternatively, the machine glazed paper may have a width of 560 to 640 mm, such as typically when the final paper stick is a paper stick other than a stick for earplugs or a lollipop stick.

[0078] The final pressed, sealed and cut paper sticks may have a diameter of about 2.2 to 2.7 mm, such as 2.4 to 2.5 mm, and a length of about 70 to 80 mm, such as about 74 to 76 mm.

[0079] Example

[0080] Example 1

[0081] Three types of 60 gsm base papers were produced, each including 100% softwood fiber, starch, alum and rosin as disclosed in Table 1. During drying, the paper was subjected to a large diameter steam heated drying cylinder (MG cylinder) on one side, so that the paper had a rougher side.

[0082] Table 1

[0083] Fiber [wt.%] Starch [wt.%] alum rosin Ex 1 Cork 100wt.% 0.5 0.26 0.16 Ex 2 Cork 100wt.% 0.51 0.30 0.18 Ex 3 Cork 100wt.% 0.5 0.33 0.18

[0084] Each sample paper Ex1-Ex3 was evaluated and the Cobb value, air resistance, tensile strength CD / MD and bending resistance in both MD and CD directions on both sides of the sample were measured. The results are shown in Table 1 below.

[0085] Table 2

[0086] parameter unit Ex1 Ex2 Ex3 Weight <![CDATA[g / m 2 ]]> 60 60 60 Air resistance s 26.5 22.3 22.7 Tensile strength CD / MD 50.0 53.0 54.0 Cobb Top <![CDATA[g / m 2 ]]> 28.9 34.8 27.1 Cobb mesh <![CDATA[g / m 2 ]]> 28.4 37.3 29.4 Bending resistance MD Nm 70 73 76 Bending resistance CD Nm 33 41 36

[0087] The target Cobb value was achieved by reducing the amount of alum and rosin. No sizing agent was added to the paper.

[0088] Example 2

[0089] In this example, three different types of paper were used to produce paper sticks. One paper was Ex.4 according to the present invention, Comparative Example CEx1 was a non-glazed paper comprising 100% softwood fibers, and Comparative Example CEx2 was a machine-glazed paper comprising 60% softwood fibers and 40% hardwood fibers. Ex.4

[0090] Table 3

[0091]

[0092]

[0093] *Kaolin

[0094] Paper sticks were produced according to the method disclosed above. The paper sticks were cut into lengths of 71.5 mm and the cut length was 70 mm.

[0095] The bending resistance of the paper sticks was measured with an L&W bend tester from ABB, measuring the force required to bend the test piece to a predetermined angle.

[0096] The results are shown in Tables 4 and 5 below.

[0097] Table 4

[0098] Paper quality in sticks Bending resistance [mN]** Ex.4 +11.4% CEx.1 refer to CEx.2 -13.0%

[0099] **Length 20mm, angle 15°

[0100] Table 5

[0101] Paper quality in sticks Bending stiffness [mN]** Ex.4 +11.1% CEx.1 refer to CEx.2 -13.2%

[0102] **Length 20mm, angle 5°

[0103] As shown in Tables 4 and 5, the bending resistance is significantly improved when paper sticks are prepared using machine-glazed papers according to the present disclosure, compared to when papers including higher amounts of hardwood fibers or non-machine-glazed papers are used.

[0104] Project List

[0105] 1. A machine glazed paper comprising softwood fibers, said machine glazed paper comprising starch in an amount ranging from 0.1 wt.% to 2 wt.% by weight of the dry weight of said machine glazed paper, having a Cobb value ranging from 20 gsm to 50 gsm measured according to standard method ISO 535:2014, and said machine glazed paper comprising 4 wt.% or less of filler.

[0106] 2. The machine-glazed paper according to item 1, wherein the machine-glazed paper comprises 3 wt.% or less filler, such as 2 wt.% or less filler, preferably 1 wt.% or less filler, more preferably 0.5 wt.% or less filler, based on the total weight of the paper. Preferably, the machine-glazed paper contains no filler.

[0107] 3. Machine-glazed paper according to item 1 or 2, wherein 63 wt.% or more of the fibers in the machine-glazed paper are softwood fibers, optionally 65 wt.% or more of the fibers in the machine-glazed paper are softwood fibers, preferably 75 wt.% or more of the fibers in the machine-glazed paper are softwood fibers, more preferably 85 wt.% to 100 wt.% of the fibers in the machine-glazed paper are softwood fibers.

[0108] 4. The machine-glazed paper according to item 1 or 2, wherein 95 wt.% to 100 wt.% of the fibers in the machine-glazed paper are softwood fibers, preferably 100 wt.% of the fibers in the machine-glazed paper are softwood fibers.

[0109] 5. Machine glazed paper according to any of the preceding items, wherein the content of sizing agents in the machine glazed paper is lower than 0.9 wt.%, such as lower than 0.5 wt.%, and optionally the paper is free of alkyl ketene dimer (AKD) and alkenyl succinic anhydride (ASA).

[0110] 6. Machine glazed paper according to any of the preceding items, wherein the machine glazed paper has a basis weight in the range of 35 gsm to 100 gsm, preferably in the range of 38 gsm to 85 gsm.

[0111] 7. The machine glazed paper according to any of the preceding items, wherein the machine glazed paper has a CD / MD stretch ratio of 0.5 or more.

[0112] 8. Machine glazed paper according to any of the preceding items, wherein the machine glazed paper has an MD elongation of 0.5% to 2%, preferably an MD elongation of 1% to 1.9%, measured according to standard method ISO 1924 / 3.

[0113] 9. Machine glazed paper according to any of the preceding items, wherein the CD elongation of the machine glazed paper is from 1.5% to 6.5%, preferably from 2% to 5.5%, preferably from 2% to 4.5%, measured according to standard method ISO 1924 / 3.

[0114] 10. Machine glazed paper according to any of the preceding items, wherein the machine glazed paper has a first side and a second side, the second side having a roughness of 1000 ml / min to 2500 ml / min.

[0115] 11. Machine glazed paper according to any of the preceding items, wherein the machine glazed paper has an air resistance in the range of 15 to 35 s, measured according to the standard method ISO 5636 "Paper and board - Determination of air permeability (mid range) - Part 5: Gurley method.

[0116] 12. A machine glazing paper according to any one of the preceding claims, wherein the machine glazing paper is for a paper stick, such as an earplug or a lollipop stick.

[0117] 13. Use of the machine-glazed paper according to any one of items 1 to 12 for producing paper sticks.

[0118] 14. A paper stick, such as an earplug stick or a lollipop stick, comprising or consisting of the machine-glazed paper according to any one of items 1 to 12.

[0119] 15. A method for producing a machine-coated paper according to any one of items 1 to 12, the method comprising the steps of:

[0120] - providing a suspension comprising softwood fibres and starch, the amount of said starch being in the range of 0.1 wt.% to 2 wt.% based on the total dry weight, and said machine-glazed paper comprising not more than 4 wt.% of filler;

[0121] - forming a fibrous web of said suspension;

[0122] - dewatering the fiber web;

[0123] - coating the first side of the dewatered fiber web in a coating unit, thereby forming said machine coated paper, said machine coated paper having a Cobb value in the range of 20 gsm to 50 gsm, measured according to standard method ISO 535:2014.

[0124] 16. A method for producing machine-glazed paper according to claim 15, wherein the softwood fibres in the suspension are unbleached softwood fibres.

Claims

1. A machine glazed paper comprising softwood fibers, said machine glazed paper comprising starch, said starch being present in an amount ranging from 0.1 wt.% to 2 wt.% by weight of the dry weight of said machine glazed paper, said softwood fibers being present in an amount of 63 wt.% or more of the total amount of fibers, and said machine glazed paper having a Cobb value ranging from 20 gsm to 50 gsm, measured according to standard method ISO 535:2014.

2. The machine-coated paper according to claim 1, wherein: The machine glazed paper comprises 4 wt.% or less filler, such as 3 wt.% or less filler, preferably 2 wt.% or less filler, more preferably 1 wt.% or less filler, based on the total weight of the paper. Preferably the machine glazed paper contains no filler.

3. The machine-coated paper according to claim 1 or 2, wherein: 65 wt.% or more of the fibers in the machine glazed paper are softwood fibers, preferably 75 wt.% or more of the fibers in the machine glazed paper are softwood fibers, more preferably 85 wt.% to 100 wt.% of the fibers in the machine glazed paper are softwood fibers.

4. The machine-coated paper according to claim 1 or 2, wherein: 95 wt.% to 100 wt.% by weight of the fibers in the machine glazed paper are softwood fibers, preferably 100 wt.% of the fibers in the machine glazed paper are softwood fibers.

5. A machine-coated paper according to any one of the preceding claims, wherein The paper may contain machine glazing paper sizing agents such as in an amount below 0.9 wt.%, such as in an amount of 0.3 wt.% or less, and optionally, the paper may be free of alkyl ketene dimer (AKD) and alkenyl succinic anhydride (ASA).

6. A machine-coated paper according to any one of the preceding claims, wherein The machine glazed paper has a basis weight in the range of 35 gsm to 100 gsm, preferably in the range of 38 gsm to 85 gsm.

7. A machine-coated paper according to any one of the preceding claims, wherein The machine-glazed paper has a CD / MD stretch ratio of 0.5 or more.

8. A machine-coated paper according to any one of the preceding claims, wherein The machine glazed paper has an MD elongation of 0.5% to 2%, preferably an MD elongation of 1% to 1.9%, measured according to standard method ISO 1924 / 3.

9. A machine-coated paper according to any one of the preceding claims, wherein: The machine glazed paper has a CD stretch of 1.5% to 6.5%, preferably a CD stretch of 2% to 5.5%, preferably a CD stretch of 2% to 4.5%, measured according to standard method ISO 1924 / 3.

10. A machine-coated paper according to any one of the preceding claims, wherein The machine glazed paper has a first side and a second side, the second side having a roughness of 1000 ml / min to 2500 ml / min.

11. Machine-coated paper according to any of the preceding items, wherein: The machine glazed paper has a first side and a second side, the first side being a glazed side and having a roughness of 100 ml / min to 400 ml / min.

12. A machine-coated paper according to any one of the preceding claims, wherein The machine-glazed paper has an air resistance in the range of 15 to 35 s, measured according to the standard method ISO 5636 "Paper and board - Determination of air permeability (mid range) - Part 5: Gurley method.

13. A machine-coated paper according to any one of the preceding claims, wherein The machine glazed paper is used for paper sticks, such as earplugs or lollipop sticks.

14. Use of a machine-glazed paper according to any one of claims 1 to 12 for producing paper sticks.

15. A paper stick, such as an earplug stick or a lollipop stick, comprising or consisting of a machine-glazed paper according to any one of claims 1 to 12.

16. A method for producing a machine-coated paper according to any one of claims 1 to 12, the method comprising the steps of: - providing a suspension comprising softwood fibers and starch, the amount of starch being in the range of 0.1 wt.% to 2 wt.% based on the total dry weight, and the amount of softwood fibers in the suspension being 63 wt.% or more of the total amount of fibers; - forming a fibrous web of said suspension; - dewatering the fiber web; - coating the first side of the dewatered fiber web in a coating unit, thereby forming said machine coated paper, said machine coated paper having a Cobb value in the range of 20 gsm to 50 gsm, measured according to standard method ISO 535:2014.

17. The method according to claim 16, wherein: The method comprises a pre-drying step between the dewatering step and the glazing step, wherein the fiber web is pre-dried in the pre-drying step to have a moisture content in the range of 40 to 60 wt.%.

18. A method for producing a machine-coated paper according to claim 15, wherein: The softwood fibers in the suspension are unbleached softwood fibers.